Pembingkaian Pesan Kulit Putih Pada Iklan Produk Kecantikan Citra Body Lotion dan Vaseline - sifwah maharani; Abiyya Sagara; Radenda Arief Mauluda (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
Beauty product advertisements have become an interesting issue for the public from time to time. In the past five years, the popularity of beauty product advertisements has become increasingly diverse and amazing. This has affected the way women interpret their bodies and themselves through the messages conveyed in these advertisements, a number of slogans and new terms have emerged as doctrines for women. This paper takes a position to display beauty product advertisements with a critical paradigm. This paper is of the opinion that advertisements for beauty products cannot be the only benchmark for women in assessing beauty in terms of body, skin, face and other aspects that may be related to women's attitudes when faced with these issues. This paper also tries to show how advertisements for beauty products in society change women's views of themselves or others regarding many things, one of which is skin color. Many women believe that by having white skin they can gain more confidence to call themselves beautiful, white skin is also often associated with the cleanliness of a woman and how society ultimately treats them. The apparatus in the subject of this study are advertisements for beauty products that are circulating outside the Instagram social media. Meanwhile, the media used as the subject in this study is to compare two advertisements for beauty products that have different concepts and branding. By taking the example of Citra body lotion and Vaseline advertisements, this paper argues that there are two types of advertisements that convey two different messages about the meaning of beauty as branding. This paper uses a critical paradigm, a qualitative approach, with a method in the form of content analysis. This study uses a methodology in the form of data reduction and axial coding.